2012
DOI: 10.1021/ic300297p
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Electron Transfer in Os(terpyridine)-biphenylene-(bi)pyridinium Assemblies

Abstract: A series of linearly arranged donor-spacer-acceptor (D-S-A) systems 1-3, has been prepared and characterized. These dyads combine an Os(II)bis(terpyridine) unit as the photoactivable electron donor (D), a biphenylene (2) or phenylene-xylylene (3) fragment as the spacer (S), and a N-aryl-2,6-diphenylpyridinium electrophore (with aryl = 4-pyridyl or 4-pyridylium in 1 or 2/3, respectively) as the acceptor (A). Their absorption spectra, redox behavior, and luminescence properties (both at 77 K in rigid matrix and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 63 publications
(32 reference statements)
7
26
0
Order By: Relevance
“…A single reversible anodic wave at +0.89 V vs. SCE is shown. This value is similar to that reported for Os–terpy‐based species in CH 3 CN and can be attributed to a monoelectronic metal‐centered oxidation, E 1/2 (Os III/II ), of the complex 16…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…A single reversible anodic wave at +0.89 V vs. SCE is shown. This value is similar to that reported for Os–terpy‐based species in CH 3 CN and can be attributed to a monoelectronic metal‐centered oxidation, E 1/2 (Os III/II ), of the complex 16…”
Section: Resultssupporting
confidence: 88%
“…In addition, four well‐resolved reversible cathodic waves are observed, while in the same experimental window [Os(ptpy) 2 ] 2+ (ptpy = 4′‐phenyl‐2,2′:6′,2″‐terpyridine) exhibits a single reduction wave centered at –1.22 V vs. SCE in CH 3 CN 16. The potential at which the first reduction process is observed for 1 (–0.88 V vs. SCE) is significantly less negative (by ca.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Several works have already demonstrated the capability and the accuracy of DFT for the description of the electronic and geometrical features of complexes containing transition metal ions and, more particularly of Ru complexes. As a matter of fact several studies reported in literature, both fully theoretical and mixed theoretical and experimental, focused on Ru(II) complexes of technological (such as dyes for Dye Sensitized Solar Cells) [16][17][18] , biological (such as DNA intercalators) 19,20 and fundamental interest (such as compounds for photoinduced charge separation) [21][22][23][24] Since TD-DFT methods and computationally more expensive ab-initio approaches, such as post-Hartree Fock methods, provide a similar description of the photophysical properties of Ru containing complexes, not surpringly the former are currently extensively used for the investigation of the electronic properties at both the ground and the excited state of large d-transition metal complexes. [25][26] Remarkably, theoretical works concerning Ru(III) and Ru(IV) complexes are less numerous than those devoted to Ru(II) complexes and mainly related to the investigation of catalytically active compounds (both of synthetic or biomimetic relevance).…”
Section: Introductionmentioning
confidence: 99%